Antropologia rewolucji w RFN i Polsce w latach 1970–1979 w perspektywie porównawczej i historycznej - Lipold, Patrycja (Rocznik Polsko-Niemiecki, 2014)
The nineteen seventies number among the most interesting periods of post-war times. They included the Vietnam war, the Hippie movement in the United States, the Socialist movement in Western Europe and the policy of ‘Détente’ in the East-West relationships. It was the extra-parliamentary opposition that gave birth to the extreme-left (terrorist) movements in Germany and worker protests in Poland, which, in turn, set about fighting the authorities and changing the relationships in their country. It was a time of rapid, dynamic changes and involvement. In the opinion of the participants in those processes themselves, they brought about a release, they constituted an apotheosis of a freedom such as they would probably never again experience in their lifetimes. These were the years of anti-authoritarian rebellion, of risking one’s own life and of international contacts of various kinds; they were the years which were to change the two countries and their history forever. The Rote Armee Fraktion (Red Army Faction) in Germany and the Workers’ Defence Committee in Poland were the two groups which spurred the great mobilisation of the societies in both countries. They provoked the events which were talked about, which were lived, the events which, transforming themselves into a great cause-and-effect machine, introduced changes that gave rise to effects, we have continued to experience to this day. Both groups had a similar genesis; they were rooted in political opposition and revolutionary purpose and they brought about immense consequences for the two societies, for politicians and for history.